A novel security media cloud framework. (March 2019) - Li, Hao; Yang, Cheng; Liu, Jianbo
Abstract: The challenges facing media cloud mainly come from two aspects, which are data security issues (copyright management and privacy protection) and security risks caused by cloud computing. This paper analyzes the security threats that media cloud faces in providing services, building a "cloud-edge-end" media cloud service hierarchy. For the first time, this paper constructs a security media cloud framework with focus on protecting multimedia data and services. The framework contains three security boundaries, two levels of data storage protection and a security access control protocol adapted to video services. Analysis shows that the proposed framework has good security and is compatible with a variety of existing media cloud frameworks.